2016
DOI: 10.1093/jxb/erw213
|View full text |Cite
|
Sign up to set email alerts
|

YUCCA-mediated auxin biogenesis is required for cell fate transition occurring duringde novoroot organogenesis in Arabidopsis

Abstract: HighlightYUCCA family genes act in response to multiple signals in leaf explants and contribute to de novo auxin biogenesis for fate transition of regeneration-competent cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
158
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 32 publications
5
158
0
3
Order By: Relevance
“…YUCCAmediated auxin biosynthesis was shown to be ubiquitously enhanced in the mesophyll of leaf blades shortly after wounding (Chen et al, 2016). During rooting of whole leaves, we detected Pro YUC9 :GUS-enriched expression in leaf mesophyll cells at 12 hae, which progressively decreased at later time points (Supplemental Fig.…”
Section: Auxin Signaling Factors Are Required For De Novo Organ Regenmentioning
confidence: 76%
See 3 more Smart Citations
“…YUCCAmediated auxin biosynthesis was shown to be ubiquitously enhanced in the mesophyll of leaf blades shortly after wounding (Chen et al, 2016). During rooting of whole leaves, we detected Pro YUC9 :GUS-enriched expression in leaf mesophyll cells at 12 hae, which progressively decreased at later time points (Supplemental Fig.…”
Section: Auxin Signaling Factors Are Required For De Novo Organ Regenmentioning
confidence: 76%
“…A study in leaf blades has shown that YUCCA1 (YUC1) and YUC4 appear to mediate synthesis of auxin in mesophyll cells (Chen et al, 2016). If this occurred in our system, auxin would also need to be transported to cells near the wound to induce de novo root organogenesis.…”
Section: Vasculature Proliferation and Endogenous Callus Formationmentioning
confidence: 88%
See 2 more Smart Citations
“…Auxin plays pivotal roles in the control of woundinduced root regeneration (Chen et al, 2016b), and it also promotes callus formation in tissue culture (Skoog and Miller, 1957). We examined transcriptional profiles of 13 auxin biosynthesis genes including YUCCA1-10 (YUC1-10) and TRP AMINOTRANSFERASE OF ARABIDOPSIS1 (TAA1) and found activation of only YUC5 and TAA1 after wounding (Fig.…”
Section: Wound Stress Does Not Modify Overall Auxin Biosynthesis or Rmentioning
confidence: 99%